Photoalteration of macrophyte-derived chromophoric dissolved organic matter induces growth of single bacterial populations in a coastal lagoon - Piccini, C., Conde, D., Pernthaler, J. and Sommaruga, R. (My University, 2013)
Photochemical degradation is an important process involved in the decay of macrophytes, but little is known on the response of heterotrophic bacteria to the chromophoric dissolved organic matter (CDOM) derived from different plant species. Here, we assessed the effect of photoaltered CDOM derived from Schoenoplectus californicus and Ruppia maritima on the composition and production of a bacterial community from a productive subtropical coastal lagoon. Chromophoric dissolved organic matter from plants extracts was characterised by optical methods before and after exposure to natural full solar radiation. Afterwards, bacteria from the lagoon were added and incubated in these extracts for 5 h. We found that CDOM from the plant extracts underwent photoalteration after exposure to natural solar radiation, inducing shifts in the original bacterial community composition. In both macrophyte extracts, the bacterial community significantly changed and became dominated by two populations with distinctive morphology. The main enriched bacteria in both plant extracts were large filaments that made up to 99% of the community biovolume. In the R. maritima extract, another type of enriched bacteria was detected, consisting of large rods. 16S rDNA sequencing showed that the enriched bacterial populations belonged to Exiguobacterium sp. (filaments) and Acinetobacter sp. (rods). Morphotype identities were confirmed by fluorescence in situ hybridisation using specific probes targeting those taxa. Our results suggest that solar-induced photoalteration of plant material in this coastal lagoon results in the growth of opportunistic bacterial taxa.
Keywords: Chromophoric dissolved organic matter, macrophytes, Exiguobacterium, Acinetobacter, coastal lagoon